Conductive Hydrogel Electrodes for Delivery of Long-Term High Frequency Pulses - Staples, Naomi A.; Goding, Josef A.; Gilmour, Aaron D.; Aristovich, Kirill Y.; Byrnes-Preston, Phillip; Holder, David S.; Morley, John W.; Lovell, Nigel H.; Chew, Daniel J.; Green, Rylie A. (Frontiers in Neuroscience, 2018)
Nerve block waveforms require the passage of large amounts of electrical energy at the neural interface for extended periods of time. It is desirable that such waveforms be applied chronically, consistent with the treatment of protracted immune conditions, however current metal electrode technologies are limited in their capacity to safely deliver ongoing stable blocking waveforms. Conductive hydrogel (CH) electrode coatings have been shown to improve the performance of conventional bionic devices, which use considerably lower amounts of energy than conventional metal electrodes to replace or augment sensory neuron function. In this study the application of CH materials was explored, using both a commercially available platinum iridium (PtIr) cuff electrode array and a novel low-cost stainless steel (SS) electrode array. The CH was able to significantly increase the electrochemical performance of both array types. The SS electrode coated with the CH was shown to be stable under continuous delivery of 2mA square pulse waveforms at 40,000 Hz for 42 days. CH coatings have been shown as a beneficial electrode material compatible with long-term delivery of high current, high energy waveforms.